Preference indices for shrubs browsed by white-tailed deer (Odocoileus virginianus) in northeastern Mexico - Segura Carmona, Juan Emmanuel; Bernal Barragán, Hugo; Carrera Treviño, Rogelio; Ibarra Gil, Humberto (Universidad Autónoma Chapingo, 2020)
The Texas white-tailed deer (Odocoileus virginianus texanus) is a selective and opportunistic ruminant that can consume over 100 plant species in its diet throughout the year. However, the white-tailed deer’s diet is made up of less than 10 species, mainly shrub species, in southern Texas and northeastern Mexico. The objectives of the study were to compare dry matter-based consumption and the shrub selectivity index for white-tailed deer and to study the relationships between some physical and chemical characteristics of shrubs that may affect consumption. A total of four white-tailed deer were involved. Shrub branches were offered for 15 minutes. Leucaena leucocephala, Acacia farnesiana and Acacia rigidula were the most consumed species; furthermore, a negative relationship between iron content and consumption rate, and a negative relationship between consumption and stem percentage were found.